Allelic-Specific Regulation of xCT Expression Increases Susceptibility to Tuberculosis by Modulating microRNA-mRNA Interactions - Wenfei Wang (American Society for Microbiology, 2020)
ABSTRACT xCT forms part of the xc− cysteine-glutamate antiporter which inhibits antimicrobial inflammatory immune functions and thus increases susceptibility to tuberculosis (TB). However, the associations between xCT gene polymorphisms and susceptibility to TB, as well as whether these modulate xCT expression or affect treatment with the xCT inhibitor sulfasalazine (SASP), are unclear. In the present study, we genotyped xCT polymorphisms in a large Chinese cohort and found that the single-nucleotide polymorphism (SNP) rs13120371 was associated with susceptibility to TB. The rs13120371 AA genotype was strongly associated with an increased risk of TB and increased xCT mRNA expression levels compared to those with the GG or AG genotype. rs13120371 is located on the 3′ untranslated (UTR) region of the xCT gene, in the putative binding site for miR-142-3p, and the results of luciferase reporter assays indicated that the rs13120371 AA genotype inhibited the binding of miR-42-3p to xCT. Bacterial burden was also significantly higher in cells with the AA genotype than in those with the GG genotype. Furthermore, pretreatment with SASP alleviated this burden in cells with the AA genotype but conferred no benefit in cells with the GG phenotype. In summary, we identified a functional SNP (rs13120371) in the xCT 3′ UTR region that increases susceptibility to TB through interacting with miR-142-3p. IMPORTANCE Tuberculosis (TB) is the leading cause of death from a single infectious agent globally, and the development of multidrug resistance represents a serious health concern, particularly in the developing world. Novel effective treatments are urgently required. xCT expression is known to increase susceptibility to TB, and certain polymorphisms in the gene encoding this protein interrupt the binding of microRNA and prevent its suppression. Taking advantage of the FDA approval for the use of sulfasalazine (SASP), which inhibits xCT-mediated cystine transport in humans, we demonstrate how host genotype-specific therapies tailored to the xCT genotype can improve TB outcomes.